2020
DOI: 10.1088/2057-1976/aba133
|View full text |Cite
|
Sign up to set email alerts
|

Interior photon counting computed tomography for quantification of coronary artery calcium: pre-clinical phantom study

Abstract: Computed tomography (CT) is the reference method for cardiac imaging, but concerns have been raised regarding the radiation dose of CT examinations. Recently, photon counting detectors (PCDs) and interior tomography, in which the radiation beam is limited to the organ-of-interest, have been suggested for patient dose reduction. In this study, we investigated interior PCD-CT (iPCD-CT) for non-enhanced quantification of coronary artery calcium (CAC) using an anthropomorphic torso phantom and ex vivo coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Future research should investigate the possible dose reductions when using a torso phantom and interior tomography imaging geometry. 57 This geometry can induce further dose reductions, 5 but it requires additional image processing, such as sinogram extension techniques, 58 to reduce the characteristic truncation artifacts originating from the limited field-of-view. Further research is also needed to expand these results for more realistic cardiac PC-FDCT and clinical CT studies with the torso and a moving heart rather than a cylindrical cardiac rod phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate the possible dose reductions when using a torso phantom and interior tomography imaging geometry. 57 This geometry can induce further dose reductions, 5 but it requires additional image processing, such as sinogram extension techniques, 58 to reduce the characteristic truncation artifacts originating from the limited field-of-view. Further research is also needed to expand these results for more realistic cardiac PC-FDCT and clinical CT studies with the torso and a moving heart rather than a cylindrical cardiac rod phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Dual energy computed tomography (DECT) utilizes two X-ray spectra to obtain two CT datasets and offers the possibility to exploit spectral information for diagnostic purposes. Compared with conventional CT, DECT is able to discriminate and qualify different materials such as soft tissues, bone and contrast agents in clinical application, for calcium density measurement, kidney stone composition determination, fragile plaques characterization and virtual non-contrast imaging [1][2][3][4] . Meanwhile, it is difficult for DECT to obtain multi-material decomposition (MMD) because the number of spectra is limited to two.…”
Section: Introductionmentioning
confidence: 99%
“…In interior computed tomography (CT), the field-ofview (FOV) is focused on the studied organ, e.g., in cardiac imaging applications, the x-ray beam is collimated to the heart (Wang and Yu 2013). This results in a reduced radiation dose to the surrounding tissues (Wang et al 2019, Juntunen et al 2020b. Also, cost savings to the imaging hardware can be attained, as the detector size can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies focus on performing CAC scoring with PCD-CT using human or anthropomorphic phantoms (Symons et al 2019, Juntunen et al 2020b. Symons et al (2019) showed the CAC scoring performance is similar as with the conventional CT, and further, the image quality can be improved with the PCDtechnology.…”
Section: Introductionmentioning
confidence: 99%